2021
DOI: 10.1002/apj.2650
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, thermodynamic and ultrasonic properties of pseudo‐binary mixtures of organic extractants and vegetable oil at 25–60°C under atmospheric pressure

Abstract: This work is intended to investigate the molecular interactions and transport properties of five pseudo‐binary mixtures of various combinations of vegetable oils (sesame oil and sunflower oil) and organic extractants (Aliquat 336, TBP, D2EHPA and TOA) by determining their surface tension, density and viscosity over a temperature range of 25–60°C at atmospheric pressure. The experimental data are fitted into various literature models. Information on excess molar volume and viscosity deviation leads to an unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The organic phase consists of a mixture of sesame oil and Aliquat 336. This mixture has been selected based on the previous research work that indicated a strong intermolecular interaction between sesame oil and Aliquat 336 due to which Aliquat 336 is immobilized within the organic phase without being adversely affected to perform its function as an extractant [36].…”
Section: Transport Methodologymentioning
confidence: 99%
“…The organic phase consists of a mixture of sesame oil and Aliquat 336. This mixture has been selected based on the previous research work that indicated a strong intermolecular interaction between sesame oil and Aliquat 336 due to which Aliquat 336 is immobilized within the organic phase without being adversely affected to perform its function as an extractant [36].…”
Section: Transport Methodologymentioning
confidence: 99%